Advances in Resist Materials and Processing Technology XXVI 2009
DOI: 10.1117/12.813990
|View full text |Cite
|
Sign up to set email alerts
|

Main chain decomposable star shaped polymer for EUV resist

Abstract: The Extreme Ultra Violet lithography (EUVL) is expected to be the most promising semiconductor fabrication technology for 22 nm node and beyond. Kozawa and his colleagues have documented that non-constant acid diffusion coefficient have a significant impact on the latent image quality of 22 nm patterns.[1] We prepared a novel main chain decomposable star shaped polymer (STAR polymer) to examine the concept. STAR polymer consists of a core unit and several arm units which connect to the core unit as shown in Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…These properties, however, have been found to be inversely related, a relationship commonly referred to as the RLS trade-off [1]. To overcome the RLS trade-off, the lithographic community is investigating alternative resist platforms such as molecular glasses [2][3][4], polymer-bound photoacid generators (PAGs) [5][6][7], and chain-scission polymers [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…These properties, however, have been found to be inversely related, a relationship commonly referred to as the RLS trade-off [1]. To overcome the RLS trade-off, the lithographic community is investigating alternative resist platforms such as molecular glasses [2][3][4], polymer-bound photoacid generators (PAGs) [5][6][7], and chain-scission polymers [8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the decomposition behavior of the STAR polymer induced by photo acid, the thermal properties of the STAR polymer film in exposed and unexposed area and lithographic performance using Micro Exposure Tool (MET) in previous paper [9]. From these results, it's found that the STAR polymer could work as main chain decomposable polymer and have a possibility to achieve better lithographic performance than the conventional linear polymer.…”
Section: Introductionmentioning
confidence: 84%
“…TF was determined as the temperature at which a CD shrink of 10% was observed as compared to a wafer without a post bake according to the same manner reported in previous paper. [9][10] Characteristics of the polymers are summarized in Table 1 For TF measurement, two different kinds of TF are investigated. The TF measured using the wafer where 170 nm hole feature is fabricated is Pre-TF.…”
Section: Preparation Of the Polymersmentioning
confidence: 99%
“…To reach the ITRS target, a reduction of 50% is required. Many studies have been doing on both optical equipment (source 5,6 , mask 7,8 , optical system 9 ) and photo materials (resist composition 10,11,12,13,14,15,16,17 , development process chemistry 18 ) in order to reduce LWR. Even combining them, it's not possible to reach the sub-32nm node ITRS targets, yet.…”
Section: Introductionmentioning
confidence: 99%